Spectroscopy (Andover: Cengage Learning, 2007)
Gain an understanding of the latest advances in spectroscopy with the text that has set the unrivaled standard for more than 30 years: Pavia/Lampman/Kriz/Vyvyan's SPECTROSCOPY. This comprehensive resource provides an unmatched systematic introduction to spectra and basic theoretical concepts in spectroscopic methods that create a practical learning resource whether you're an introductory student or someone who needs a reliable reference text on spectroscopy. This well-rounded introduction features updated spectra; a modernized presentation of one-dimensional nuclear magnetic resonance (NMR) spectroscopy; the introduction of biological molecules in mass spectrometry; and inclusion of modern techniques alongside DEPT, COSY, and HECTOR. Count on this book's exceptional presentation to provide the comprehensive coverage you need to understand today's spectroscopic techniques.
Appendices 1-10, 603-682p.; Index 683-690p.
Keywords: Spectroscopy